Academic freedom : autonomy, challenges and conformation - Ceglie, Robert; Thompson, Sherwood (Emerald Publishing, 2021)
Framed in the context of a world in which academic freedom is often jeopardized, or criticized by outside social forces, Academic Freedom: Autonomy, Challenges and Conformationsets out to echo the voices of faculty who have encountered challenges to academic freedom within their personal and professional careers.